Kohesi Leksikal Ekspresi Pemberontakan pada Circe karya Madeline Miller - Garnida, Susie Chrismalia; Sudarwati, Sudarwati; Rahayu, Anik Cahyaning; Bay Kurniawan, Adelt Fricilia (Universitas 17 Agustus 1945 Surabaya, 2024)
Lexical cohesion refers to the way in which words in a text relate to each other through their meanings. This topic is important due to the fact that words in texts have relations among them based on the keywords. The relation could be in synonymy, antonymy, and hyponymy, which sometimes some readers lack of this matter. The subject of this study is the literary work of the novel Circe by Madeline Miller. The focus of this study is how lexical cohesion supports themes of rebellion in this novel and demonstrates how vocabulary forms a network. This study answers the gap in existing research, which mostly explores lexical cohesion in educational contexts and journal articles, but not in literary works with certain themes such as rebellion. This study aims to identify and analyze the lexical cohesions used to convey the theme of rebellion in the novel Circe and, with existing data, investigate how lexical cohesion forms vocabulary networks. This study used Halliday and Matthiessen's (2014) theory of lexical cohesion. This analysis reveals how lexical choices increase narrative coherence and thematic depth. The methodology used is qualitative research. The source of this study is Madeline Miller's Circe. The findings show that lexical cohesion in Circe is 50 data achieved through various devices such as synonymy (five nouns, four verbs, four adjectives), antonymy (seven nouns, five verbs, four adjectives), and hyponymy (nine nouns, twelve verbs, zero adjectives). This lexical cohesion demonstrates how vocabulary forms a network that enhances understanding and vocabulary by forming a network of related words such as synonyms, antonyms, and hyponyms that help readers or listeners connect ideas, identify relationships between terms, and interpret texts more coherently, ultimately enriching comprehension and enabling the acquisition of diverse and nuanced word meanings.